GCMS identification of volatile compounds in Indonesia’s specific traditional “kalio” and dried rendang - Rini Rini; Daimon Syukri; Fauzan Azima (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2020)
Rendang is a traditional-specific food in Indonesia. Rendang is generally made with beef, coconut milk, and spices. There are two types of rendang according to its time processing. Rendang “kalio” is a final product of rendang that needs a short heating period while dried rendang is produced by the longer heating period. In the present study, the profile of the volatile compounds that most obtained from spices was analyzed by gas chromatography-mass spectrometry (GC-MS) to characterize the influence of the cooking period on the flavor characteristic of two available types of rendang. There were dozens of volatile compounds identified including carboxylic, aromatic, carbonyl, and alcohols where carboxylic and aromatics were the predominant volatile fractions. The results indicated that the cooking period affected the profile of volatile compounds between "kalio" rendang and dried rendang. Carboxylic and aromatics were less in the dried rendang compared to the rendang “kalio” where others were opposites. The increase of carbonyls and alcohol during the cooking process has suggested can play a crucial role in the flavor of dried rendang.